Profile Analysis of Basic Science Process Skills for Grade 8 Junior High School Students at SMP Negeri 2 Sembawa - Rahmi Susanti; Hartono Hartono; Melly Ariska; Sunyono Sunyono; Viyanti Viyanti; Dina Maulina; Nurjannah Nurjannah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
Students benefit from science process skills when students try and try to solve problems from the instruments that have been disseminated through this research. To overcome student problems that occur in the classroom during the learning process, they must acquire adequate science process skills. Teachers must be able to understand the skills well so that students can get the needed needs. This study aims to determine the profile of science process skills of VIII grade junior high school students at SMP Negeri 2 Sembawa. The results of this study are expected to be used as a guide for science teachers at SMP Negeri 2 Sembawa in overcoming students' difficulties in mastering science concepts in schools. This quantitative research was conducted by testing using the Basic Skill Process (BAPS) instrument. The research sample consisted of 81 junior high school students in class VIII at SMP Negeri 2 Sembawa. Researchers obtained learning data based on the results of the Science Process Skills (SPS) test. The SPS test consists of 25 understanding of SPS concepts. The results of the study revealed that the percentage results of students' process skills for each indicator were observing 28.39%, communicating 63.20%, classifying 61.23%, predicting 49.91%, and inferring 40.74%. Based on these percentages, it can be seen that the highest indicators achieved by students are indicators of communication and classification, while the lowest indicators achieved by students are indicators of observation and data inference. The category of mastery of science process concepts for SMP Negeri 2 Sembawa students is included in the medium category. the quality of learning to improve the ability to observe students by increasing the ability of the five senses. Learning that involves a lot of students' sensory abilities is also needed to stimulate science process skills to be achieved properly.